Amiodarone treatment in cats: evaluation of indications, adverse effects, and survival outcomes - Rossi, Graham C.; Tjostheim, Sonja S.; Kellihan, Heidi B.; Stepien, Rebecca L.; Liou, Michael; Marshall, Cecilia; Wright, Kathy N. (Frontiers in Veterinary Science, 2025)
IntroductionTime-and dose-dependent adverse effects of amiodarone have not been described in cats. The primary aim of this retrospective multicenter cohort study was to report the type and frequency of clinical adverse effects and biochemical changes in cats receiving amiodarone chronically. The secondary aim was to report survival outcomes in this population of cats.MethodsMedical records were reviewed for signalment, arrhythmia diagnosis, presence of structural heart disease, systemic comorbidities and congestive heart failure at presentation, amiodarone dose, serial bloodwork results, adverse events, and survival outcome.ResultsThe study population included 27 client-owned cats (2016–2022). All cats had structural cardiac disease, and many were in congestive heart failure (17/27; 63%) at presentation. Amiodarone was most commonly prescribed for ventricular tachycardia (19/27, 70%), and it was administered once daily with a median [range] dose of 8.8 [4.515.2] mg/kg/day. There was a decrease in serum concentration of alanine transaminase between pretreatment values and values measured during the early amiodarone treatment window, 1–90 days (n = 16; p = 0.034). No statistical difference in serum concentration of alanine transaminase (n = 10; p = 0.799) was noted after 90 days of treatment compared to pretreatment. There was no change in hematocrit, neutrophil count, and serum concentration of alkaline phosphatase and total thyroxine during treatment in assessed cats. Ten cats (37%) had at least one episode of hyporexia or vomiting while receiving amiodarone. The median survival time for all-cause mortality was 441 days (95% confidence interval, 126–929 days); cats in which the primary therapeutic target was both supraventricular and concomitant ventricular tachyarrhythmias had at least a two-fold risk of dying compared to cats with supraventricular tachyarrhythmias alone (hazard ratio 12.9, 95% CI 1.86–89.8; p = 0.010).DiscussionAmiodarone was primarily used to treat ventricular arrhythmias. Transient gastrointestinal signs were reported in approximately one-third of the cats studied, but no clinically significant laboratory abnormalities were found in cats receiving amiodarone.